In Vitro Plant Regeneration from Commercial Cultivars of Soybean. (11th June 2017) - Raza, Ghulam; Singh, Mohan B.; Bhalla, Prem L.
Abstract : Soybean, a major legume crop, is the source of vegetable oil and protein. There is a need for transgenic approaches to breeding superior soybean varieties to meet future climate challenges. Efficient plant regeneration is a prerequisite for successful application of genetic transformation technology. Soybean cultivars are classified into different maturity groups based on photoperiod requirements. In this study, nine soybean varieties belonging to different maturity group were regenerated successfully from three different explants: half split hypocotyl, complete hypocotyl, and cotyledonary node. All the genotypes and explant types responded by producing adventitious shoots. Shoot induction potential ranged within 60–87%, 50–100%, and 75–100%, and regeneration rate ranged within 4.2–10, 2.7–4.2, and 2.6–10.5 shoots per explant using half split hypocotyl, complete hypocotyl, and cotyledonary explants, respectively, among all the tested genotypes. Bunya variety showed the best regeneration response using half split and complete hypocotyl explants and the PNR791 with cotyledonary node. The regenerated shoots were successfully rooted and acclimatized to glasshouse conditions. This study shows that commercial varieties of soybean are amenable to shoot regeneration with high regeneration frequencies and could be exploited for genetic transformation. Further, our results show no correlation between shoots regeneration capacity with the maturity grouping of the soybean cultivars tested.